2017
DOI: 10.1007/s00216-017-0724-9
|View full text |Cite
|
Sign up to set email alerts
|

Multianalyte, high-throughput liquid chromatography tandem mass spectrometry method for the sensitive determination of fungicides and insecticides in wine

Abstract: Evidence of pesticide transfer from grapes to wine, added to differences in the national regulations regarding the number and the maximum concentration of these species in wine, demands analytical procedures suitable for their routine control in this foodstuff. In this research, solid-phase extraction (SPE) and ultra-performance liquid chromatography (UPLC), with tandem mass spectrometry (MS/MS) detection, are combined to obtain a sensitive and rapid procedure to determine 50 pesticides in red and white wines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
2
15
2
Order By: Relevance
“…For the rest of compounds, LOQs remain three orders of magnitude below MRLs for grapes. When compared with values achieved in previous studies, the LOQs compiled in Table 3 are significant lower than those reported for SPE techniques (from 0.1 to 15 ng mL -1 , depending on the compound) [9,10] and also than those reported for QuEChERS (ca.…”
Section: Methods Performancementioning
confidence: 49%
See 4 more Smart Citations
“…For the rest of compounds, LOQs remain three orders of magnitude below MRLs for grapes. When compared with values achieved in previous studies, the LOQs compiled in Table 3 are significant lower than those reported for SPE techniques (from 0.1 to 15 ng mL -1 , depending on the compound) [9,10] and also than those reported for QuEChERS (ca.…”
Section: Methods Performancementioning
confidence: 49%
“…The relative deviations of retention times through a typical sequence, involving more than 50 injections, remained below 0.15% for all the compounds. Additional instrumental parameters, including ESI variables were adopted from a previous study [10].…”
Section: Lc-esi-ms/ms Parametersmentioning
confidence: 99%
See 3 more Smart Citations